Numerical investigations, development and control of a cartesian (3-PRRR) parallel manipulator. (August 2022) - John, Isaac; Mohan, Santhakumar; Rybak, Larisa
This paper focusses on the development of a Cartesian parallel manipulator (CPM) having multiple limb assembly configurations. An optimal configuration of the 3-PRRR CPM is identified after analysing the interference-free workspace of various limb assembly conditions, where each leg comprises an active prismatic joint followed by three revolute joints. The validation of the link interference detection algorithm is carried out using a virtual prototype. The Euler–Lagrange dynamic modelling of the CPM is validated using one of the well-known multi-body simulation packages namely, ADAMS. The paper proposes a detailed design and performance analyses of a motion controller for the proposed manipulator, based on a finite-time sliding mode scheme. A Graphical User Interface (GUI) is also developed using the MATLAB App Designer, which ensures easier and intuitive synthesis of the CPM. The development of an in-house functional prototype is also presented in this work.